Growth substrates change the decomposition process of eelgrass in water bodies - Wen Wang; Enqi Liu; Chunzhen Fan; Min Zhao; Zhiquan Wang; Zhan Jin; Ke Bei; Xiangyong Zheng; Suqing Wu; Ye Tang; Chang Yang (Environmental Sciences Europe)
Abstract Decomposition of submerged plants releases organic matter, nitrogen, and phosphorus into water bodies, generating an important impact on the aquatic ecosystem. This study explored the influence of growth substrate with different compositions on the decomposition process of eelgrass (Vallisneria spinulosa Yan, V. spinulosa Yan). The sediment + iron–carbon fillers system exhibited significantly lower concentrations of total nitrogen (TN) and total phosphorus (TP) in the overlying water than other systems, with the maximum values of 5.68 and 7.05 mg/L, respectively. The addition of ceramic and calcium nitrate promoted the formation of HCl-extracted phosphorus (HCl–P) in the sediment, while the addition of iron–carbon fillers increased the content of NaOH-extracted phosphorus (NaOH–P). Three-dimensional fluorescence spectroscopy of dissolved organic matter (DOM) in overlying water showed that different substrate compositions did not significantly affect the compositions of organic matter released during the decomposition of V. spinulosa Yan. The microbial community and abundance in each experimental group changed significantly before and after the decomposition of V. spinulosa Yan. The sediment + iron–carbon fillers system showed significantly higher abundance of microbial community than other systems, with the enrichment of functional bacteria related to denitrification and sulfate reduction. In contrast, the sediment + calcium nitrate system exhibited a smaller change of microbial community abundance, with the enrichment of aerobic denitrifying bacteria. In this paper, it was found that the sediment + iron–carbon group had a good adsorption effect on nitrogen and phosphorus released during the decomposition process of V. spinulosa Yan, and had a good effect on water purification as the growth substrate of submerged plants.